Math, asked by zoha2520, 5 months ago

if 2 (a2 - b2) = (a-b)2 then show that a+b=0​

Answers

Answered by ljranjit37
0

Answer:

if 2(a2+b2)=(a+b)2,then show that a=b

Answered by Aashita48530
0

Answer:

Correction, the question must be 2 (a² + b²) = (a-b) ²

Step-by-step explanation:

2(a² + b²) = (a-b) ²

(a-b) ² = a² + b² - 2ab

2a² + 2b² = a² + b² - 2ab

2a² - a² + 2b² - b² = - 2ab

a² + b² = - 2ab

(a + b)² = a² + b² + 2ab

a² + b² = - 2ab → (a + b)²

a² + b² + 2ab

2ab + 2ab

0

(a + b)² = 0²

a + b = 0

PLEASE MARK ME AS THE BRAINIEST!!!

Similar questions